Comparison of intensity modulated proton therapy beam configurations for treating thoracic esophageal cancer. (April 2022) - Oonsiri, Sornjarod; Kitpanit, Sarin; Kannarunimit, Danita; Chakkabat, Chakkapong; Lertbutsayanukul, Chawalit; Prayongrat, Anussara
Highlights: Dosimetric benefit of proton over x-ray treatment for thoracic esophageal cancer. Reduction of pulmonary and cardiac toxicity by proton therapy. Intensity modulated proton therapy beam configurations designed by tumor location. Abstract: Background and purpose: Specific proton-beam configurations are needed to spare organs at risk (OARs), including lungs, heart, and spinal cord, when treating esophageal squamous cell carcinoma (ESCC) in the thoracic region. This study aimed to propose new intensity-modulated proton therapy (IMPT) beam configurations and to demonstrate the benefit of IMPT compared with intensity-modulated x-ray therapy (IMXT) for treating ESCC. Material and methods: IMPT plans with three different beam angle configurations were generated on CT datasets of 25 ESCC patients that were treated with IMXT. The IMPT beam designs were two commonly-used beam configurations (anteroposterior and posterior oblique) and a recently proposed beam configuration (anterosuperior with posteroinferior). The target doses were 50–54 Gy(RBE) and 60–64 Gy(RBE) to the low-risk and high-risk target volumes, respectively. Robust optimization was applied for the IMPT plans. The differences in the dose-volume parameters between the IMXT and IMPT plans were compared. Results: With target coverage comparable to standard IMXT, IMPT had significantly lower mean doses to the OARs. IMPT with an anteroposterior opposing beam generated the lowest lung dose (mean = 7.1 Gy(RBE), V20 = 14.1%) and the anterosuperior with posteroinferior beam resulted in the lowest heart dose (mean = 12.8 Gy(RBE), V30 = 15.7%) and liver dose (mean = 3.9 Gy(RBE), V30 = 5.9%). For the subgroup of patients with an inferior tumor location (PTVs overlapping a part of the contoured heart), the novel beam demonstrated the optimal OARs sparing. Conclusion: Compared with IMXT, the IMPT plans significantly reduced the radiation dose to the surrounding organs when treating ESCC. IMPT beam configuration selection depends on the tumor location relative to the heart.